Calcium aluminate cement-based blends for application to fill in bone defects - de Alcântara Abdala, Julia Marinzeck (2020)
Introduction: The need to treat bone defects is increasing dramatically as the population grows old. Calcium aluminate cement, CAC, has been applied to fill in bone defects. CAC has been used in orthopedics, as it can avoid some problems of commercial products, polymethylmethacrylate, PMMA, regarding its too low consistency and strong odor and exothermic reactions which can damage the surrounding tissue. Besides that, CAC can be molded in situ to provide intimate fitting to the defect rims. The injectability of cements is an important aspect when minimally invasive surgical techniques are used and for applications with limited accessibility and narrow cavities. Methods: At present work, CAC was initially analyzed via zeta potential and viscosity when mixed with different dispersant additives. Then, CAC blends containing different materials, alumina, zirconia, zinc oxide, hydroxyapatite, tricalcium phosphate, chitosan, collagen, or zinc oxide-bismuth oxide, were evaluated regarding their injectability and by means of in vitro mineralization and ex vivo uniaxial cold crushing strength tests. The best injectability conditions, 76 wt% solids, hypodermic needle, were used for the ex vivo tests. In the latter, the compositions selected by in vitro tests were injected to repair 3-mm defects on mouse femurs cut into pieces of 10 mm, whereas collagen and PMMA were inserted with a spatula. After setting the materials for 24 h at 37 °C in body fluid solution, the pieces were submitted to uniaxial cold crushing strength tests. Results: The blends alumina, collagen, and chitosan resulted in greater reddish-stained areas indicating enhanced mineralized matrix formation for these groups, which also presented higher values of calcium deposits indicating a successful in vitro bone-like nodule formation. Conclusion: The filling of defects with CACH and its blends increased the resistance of bones when compared to bones with the added defect, with lower effect verified in the presence of chitosan and collagen.